2003
DOI: 10.1124/jpet.103.050104
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acetylcholine Receptor-Mediated Neuroprotection by Donepezil Against Glutamate Neurotoxicity in Rat Cortical Neurons

Abstract: Donepezil is a potent and selective acetylcholinesterase (AChE) inhibitor developed for the treatment of Alzheimer's disease. To elucidate whether donepezil shows neuroprotective action in addition to amelioration of cognitive deficits, we examined the effects of donepezil on glutamate-induced neurotoxicity using primary cultures of rat cortical neurons. A 10-min exposure of cultures to glutamate followed by a 1-h incubation with glutamatefree medium caused a marked loss of viability, as determined by Trypan b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
126
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(135 citation statements)
references
References 39 publications
8
126
0
1
Order By: Relevance
“…Donepezil was developed to treat patients with Alzheimer's disease as an acetylcholinesterase inhibitor [12,13]. Donepezil prevents neurons from apoptosis and degeneration [19][20][21][22] and improves cognitive abilities in patients with Alzheimer's disease [23][24][25]. However, only few studies have focused on the angiogenesis accelerating effects of donepezil [26].…”
Section: Discussionmentioning
confidence: 99%
“…Donepezil was developed to treat patients with Alzheimer's disease as an acetylcholinesterase inhibitor [12,13]. Donepezil prevents neurons from apoptosis and degeneration [19][20][21][22] and improves cognitive abilities in patients with Alzheimer's disease [23][24][25]. However, only few studies have focused on the angiogenesis accelerating effects of donepezil [26].…”
Section: Discussionmentioning
confidence: 99%
“…The non-neuronal cholinergic system might also be involved in efficient glucose metabolism in cardiomyocytes. Additionally, a number of experimental studies strongly suggest that donepezil directly affect cells via a mechanism that is independent of its pharmacological action of acetylcholinesterase inhibition [19,[47][48][49]. Further investigation is needed to determine the molecular mechanism of the donepezil-induced increase in the efficiency of cardiac glucose utilization.…”
Section: Discussionmentioning
confidence: 99%
“…After medium was replaced with fresh conditioned Dulbecco's Modified Eagle Medium (DMEM, Wako Pure Chemical Industries, Lt., Osaka, Japan) with or without donepezil at a concentration of 10 µM, cells were further incubated at 37°C for 2-3 days. The concentration of donepezil was determined by referring to Takada et al who investigated the cell protective properties of donepezil [19]. mRNA or protein was obtained from the cultured cardiomyocytes for reverse transcription-polymerase chain reaction (RT-PCR) or Western blot analysis, respectively.…”
Section: Cardiomyocyte Isolation and Drug Treatmentmentioning
confidence: 99%
“…Donepezil powerfully inhibits acetylcholinesterase (17) and elevates acetylcholine concentration in the synapse, which results in increased cholinergic transmission. Previous studies have suggested the donepezil has neuroprotective effects aside from its acetylcholinesterase-inhibiting action through up-regulation of Bcl-2, an anti-apoptotic protein (18), stimulation of nicotinic acetylcholine receptors (19), and inhibition of glycogen synthase kinase-3 (GSK-3) activity (20). It is unknown whether donepezil exerts its neuroprotective effect in rats subjected to repeated cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether donepezil exerts its neuroprotective effect in rats subjected to repeated cerebral ischemia. Induction of the neuroprotective effects of donepezil via the nicotinic acetylcholine receptor in rats subjected to repeated cerebral ischemia may require a higher concentration and/or long-term treatment because the concentration of donepezil showing neuroprotection is higher than the concentration needed to exhibit acetylcholinesterase-inhibiting action in vitro (17,19,20).…”
Section: Discussionmentioning
confidence: 99%